Effekten av klimatförändringar på kontrollbehovet av åkerogräs - Jarmakowski, Sara (SLU/Dept. of Crop Production Ecology, 2009)

(untitled)
With a changing climate, we can expect higher temperatures and more precipitation in Sweden. As the temperature increases, new weed species are expected to migrate in from more southerly latitudes, resulting in requests for new techniques for weed control. In addition, we might see a greater number of weed species and higher biomass production due to increased concentration of CO2 in the atmosphere. Increased understanding of the biology of specific weed species will become more important in future weed control. This will help to control the weeds more efficiently. Higher prices on pesticides and a public demand for reduced use of pesticides make growers more inclined to use mechanical weed control on a larger scale and to a greater extent prevent weed establishment before sowing. A well-planned crop rotation is the most important preventive measure, which might also include delayed sowing, and dark harrowing and sowing. Research takes place on many levels within the weed area and several alternative methods are being developed. These include electric current, freezing, microwaves, biological control, etc. The present work is a literature review aiming at describing how a warmer and more humid climate with a higher CO2 concentration will affect the need for weed control.